THE IMPLEMENTATION OF DBE (DECENTRALIZED BASIC EDUCATION) 3 IN ENGLISH TEACHING WRITING SKILL OF SMPN 3 COLOMADU IN 2010/ 2011 ACADEMIC YEAR - NATALIA, FIFIN (2011)
This research paper aims to describe the implementation of Decentralized Basic Education 3 in English teaching of writing skill at SMPN 3 Colomadu. Decentralized Basic Education (DBE) is a cooperative learning supported by USAID, the general aims of DBE is to improve the Equivalency Education program. At SMPN 3 Colomadu the teaching learning processes are using DBE 3 which more focuses in increasing junior secondary and non-formal education to life skill. The writer focuses on teaching learning processes, especially the second year students as the object of the study. The method of collecting data is descriptive by employing interview, observation, and field note. The results of the research are the implementation of English teaching of writing skill using DBE, first, the students are more active to communicate in the class, they can explore their ideas more and thought in their writing skill. Second, DBE 3 can increase the student interest and attention. Third, DBE 3 can make the process of teaching writing skill easier.